The effects of generalized joint laxity on risk of anterior cruciate ligament injury in young female athletes - Myer, G. D.; Ford, K. R.; Paterno, M. V.; Nick, T. G.; Hewett, T. E. (The American Journal of Sports Medicine, 2008)
Women who participate in high-risk sports suffer anterior cruciate ligament injury at a 4- to 6-fold greater rate than men.